Pre-eclampsia and the risk of autism-spectrum disorder in offspring: Meta-analysis - Dachew, B.; Mamun, A.; Maravilla, J.; Alati, Rosa (Royal College of Psychiatrists, 2018)
© 2018 The Royal College of Psychiatrists. Background: Evidence about the effect of intrauterine exposure to preeclampsiaon offspring autism-spectrum disorder (ASD) is notwell established.Aims: To examine the association between pre-eclampsia and ASD.Method: PubMed, Embase and PsycINFO databases were searched.Pooled relative risks (RR) with 95% confidence intervals werecalculated. Subgroup and sensitivity analyses were performed.Heterogeneity was assessed using Cochran's Q- and the I2-test.The presence of publication bias was evaluated by Egger's testand visual inspection of the symmetry in funnel plots.Results: Ten studies meet the inclusion criteria. The risk of ASD was 32%higher in offspring who had intrauterine exposure to preeclampsiacompared with those not exposed (RR = 1.32, 95% CI1.20-1.45). Sensitivity analysis revealed consistent pooled estimatesranging from RR = 1.30 (95% CI 1.17-1.44) to RR = 1.37(95% CI 1.26-1.48). We found no significant heterogeneity andevidence of publication bias. Conclusion: Pre-eclampsia increased the risk of ASD in offspring. The findingsuggests a need for early screening for ASD in offspring ofwomen with pre-eclampsia.